Investigation of convection and diffusion during biodiesel production in packed membrane reactor using 3D simulation - Sajjadi, Baharak; Abdul Raman, Abdul Aziz; Baroutian, Saeid; Ibrahim, Shaliza (Elsevier, 2014)
The 3D simulation of convection and diffusion phenomena within a ceramic membrane during transesterification reaction was the aim of this study. The ceramic membrane was a tubular micro porous TiO2/Al2O3 packed with the heterogeneous catalyst. The Navier–Stokes, Brinkman and Stephan–Maxwell equations were applied for investigation of fluid flow reaction and mass transfer within the system. The value of the convection was generally between 104 and 107 times higher than diffusion. It depends on concentration component, the diffusion coefficient and components velocity. A good agreement was found with the maximum deviation of 8% from experimental data.